VD_FINDINFO Arrêt / 2022 / 71 vom 14. Januar 2022 - VD Tribunal cantonal (2022)
FRAIS JUDICIAIRES, DÉPENS, ASSISTANCE JUDICIAIRE | 69 al. 1bis LAI, 61 let. a LPGA, 61 let. g LPGA, 94 al. 1 let. a LPA-VD